Sibling Position and Risk Attitudes: Is Being an Only Child Associated with a Person’s Risk Tolerance? - Jennifer M Brown M.S.; John E Grable Ph.D., CFP® (Journal of Financial Therapy, 2015)
The influence of birth order on personality has been studied for several decades, but little research has been conducted on the association between sibling position and risk tolerance. The purpose of this study was to examine the relationship between being an only child and risk-taking attitudes. Data from the 2010 National Longitudinal Survey of Youth, 1979 sample was used to test the hypotheses that only children and first borns are similar, only children exhibit a lower risk tolerance when compared to those with siblings, and only children exhibit a lower risk tolerance when compared to those with siblings when first borns are removed and only borns are compared with later borns. Results did show that only children are similar to first borns in nearly every domain of risk tolerance considered. Furthermore, they do not exhibit dramatically different risk attitudes than those with siblings when the variables of sex, locus of control, and net worth are controlled.
Keywords: risk tolerance; birth order; self-assessed risk; life change risk